Hubungan Kualitas Tidur dengan Caring Perawat dalam Pelayanan Asuhan Keperawatan di RSD Idaman Kota Banjarbaru - Ellysia Yulanda; Herry Setiawan; Ichsan Rizany; Herry Setiawan (Poltekkes Kemenkes Bengkulu, 2021)
Nurses are required to provide excellent and quality service for 24 hours including at rest hours, requiring nurses to be in good body condition. Sleep quality is an important indicator of health and well-being in nurses. Caring attitudes towards patients indirectly improve the quality of nurse performance, quality of service and client satisfaction in the hospital.The purpose of the study was to find out the relationship of sleep quality with caring nurses in nursing care services at Idaman Hospital in Banjarbaru City. Research uses methods that are correlation and cross sectional approach with sample probability sampling technique and simple random sampling type.Research sample of 70 implementing nurses in the inpatient room of Idaman Hospital in Banjarbaru City. The data was taken by providing a PSQI questionnaire and a caring questionnaire. The analysis test uses the Spearman correlation test. The results of this study described the average nurse's sleep quality as much as 7.03 and caring nurses on average as much as 113.04.The results of the analysis obtained a negative directional relationship between the quality of nurse sleep and caring nurses in nursing care services at Idaman Hospital in Banjarbaru City (p value = 0.013<0.05).The quality of sleep can affect caring nurses in doing nursing care so that it is expected that nurses will be more able to provide nursing care services in order to increase the status of trust and patient health.